Toner and method for manufacturing toner
Patent Information
- Application Number
- JP2023132550
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-08-16
- Publication Date
- 2025-02-28
AI Technical Summary
【0009】 本発明に係るトナー及びトナーの製造方法は、帯電性に優れると共に、クリーニング不良の発生を抑制できるトナーを提供できる。
Smart Images

Figure 2025027621000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a toner and a method for producing a toner. [Background technology]
[0002] In electrophotographic image forming apparatuses, toner containing positively charged toner particles is used. The toner is required to have excellent charging properties. In addition, electrophotographic image forming apparatuses form images by transferring the toner developed on the photosensitive drum to a recording medium. However, a part of the toner developed on the photosensitive drum is not transferred to the recording medium and remains on the photosensitive drum as residual toner. Therefore, electrophotographic image forming apparatuses may be provided with a mechanism (for example, a cleaning blade) for cleaning the residual toner present on the photosensitive drum. In electrophotographic image forming apparatuses, when a phenomenon occurs in which the residual toner cannot be sufficiently removed from the photosensitive drum (cleaning failure), image failure may occur. Therefore, the toner is required to be able to suppress the occurrence of cleaning failure.
[0003] In response to these demands, a toner manufacturing method has been proposed that includes, for example, a step of forming an emulsion containing droplets containing a resin having an acid group, a hydrophobic first solvent capable of dissolving the resin, a colorant, and a positively charged charge control agent, and an aqueous dispersion medium for dispersing the droplets, a step of forming solid particles by solidifying the droplets by removing the first solvent from the droplets in the emulsion, and a step of washing the solid particles with a second solvent capable of dissolving the charge control agent but not dissolving the resin (Patent Document 1). The toner obtained by this manufacturing method is said to have excellent chargeability. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2007-025655 A Summary of the Invention [Problem to be solved by the invention]
[0005] However, the toner obtained by the manufacturing method described in Patent Document 1 cannot sufficiently suppress the occurrence of cleaning defects.
[0006] The present invention has been made in view of the above problems, and an object of the present invention is to provide a toner that is excellent in chargeability and can suppress the occurrence of cleaning defects. [Means for solving the problem]
[0007] The toner according to the present invention includes toner particles. The toner particles include toner base particles and an external additive attached to the surface of the toner base particles. The number-average circularity of the toner base particles is 0.950 or more and 0.985 or less. The toner base particles contain a binder resin having a glass transition point of 20° C. or more and 65° C. or less, and a positively charged charge control agent. The binder resin includes a specific styrene-(meth)acrylic resin. The content of the specific styrene-(meth)acrylic resin in the toner base particles is 50.0% by mass or more and 95.0% by mass or less. The acid value of the specific styrene-(meth)acrylic resin is 2.5 mgKOH / g or more and 30.0 mgKOH / g or less.
[0008] The toner manufacturing method according to the present invention is a method for manufacturing a toner containing toner particles, and includes a toner core preparation step of preparing a toner core containing a binder resin, a shell layer formation step of obtaining toner base particles by forming a shell layer on the surface of the toner core, and an external addition step of obtaining the toner particles by attaching an external additive to the surface of the toner base particles. The glass transition point of the binder resin is 20° C. or more and 65° C. or less. The binder resin contains a specific styrene-(meth)acrylic resin. The content ratio of the specific styrene-(meth)acrylic resin in the toner base particles is 50.0% by mass or more and 95.0% by mass or less. The acid value of the specific styrene-(meth)acrylic resin is 2.5 mgKOH / g or more and 30.0 mgKOH / g or less. The shell layer contains hydrophobic resin particles and positively charged resin particles. In the shell layer formation step, the toner core, the hydrophobic resin particles, and the positively charged resin particles are dispersed at a processing temperature of 55° C. or more and 78° C. or less. Effect of the Invention
[0009] The toner and the method for producing the toner according to the present invention can provide a toner that is excellent in chargeability and can suppress the occurrence of cleaning defects. [Brief description of the drawings]
[0010] [Figure 1] FIG. 2 is a diagram illustrating an example of a toner particle. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0011] A preferred embodiment of the present invention will be described below. The toner is an aggregate (e.g., powder) of toner particles. The external additive is an aggregate (e.g., powder) of external additive particles. Unless otherwise specified, the evaluation results (values indicating shape, physical properties, etc.) of the powder (more specifically, the powder of toner particles, the powder of external additive particles, the powder of toner mother particles, the powder of toner cores, etc.) are the number averages of values measured for each of a considerable number of particles selected from the powder.
[0012] Volume median diameter of powder (D 50 ) is a value measured using a laser diffraction / scattering particle size distribution analyzer (e.g., HORIBA, Ltd.'s "LA-920V2" or Beckman Coulter, Inc.'s "Coulter Counter Multisizer 3" unless otherwise specified.
[0013] Unless otherwise specified, the number average primary particle diameter of a powder is the number average value of the circle equivalent diameters of primary particles (Heywood diameter: diameter of a circle having the same area as the projected area of a primary particle) measured using a scanning electron microscope. The number average primary particle diameter of a powder is, for example, the number average value of the circle equivalent diameters of 100 primary particles. The number average primary particle diameter of particles refers to the number average primary particle diameter of particles in the powder unless otherwise specified.
[0014] Unless otherwise specified, the chargeability refers to the chargeability in triboelectric charging. For example, a standard carrier (standard carrier for negatively charged toner: N-01, standard carrier for positively charged toner: P-01) provided by the Imaging Society of Japan is mixed with the measurement target (e.g., toner) and stirred to triboelectrically charge the measurement target. The charge amount of the measurement target is measured before and after triboelectric charging, for example, with a small suction-type charge amount measuring device (Trek's "MODEL 212HS"), and the greater the change in charge amount before and after triboelectric charging, the stronger the chargeability of the measurement target.
[0015] Unless otherwise specified, the measured value of the melting point (Mp) is the temperature of the maximum endothermic peak in an endothermic curve (vertical axis: heat flow (DSC signal), horizontal axis: temperature) measured using a differential scanning calorimeter ("DSC-6220" manufactured by Seiko Instruments Inc.) This endothermic peak appears due to melting of the crystallized site.
[0016] Unless otherwise specified, the glass transition point (Tg) is a value measured according to JIS (Japanese Industrial Standards) K7121-2012 using a differential scanning calorimeter (DSC-6220 manufactured by Seiko Instruments Inc.). In the endothermic curve measured by the differential scanning calorimeter (vertical axis: heat flow (DSC signal), horizontal axis: temperature), the temperature of the inflection point due to the glass transition (specifically, the temperature of the intersection between the extrapolated line of the baseline and the extrapolated line of the falling line) corresponds to Tg (glass transition point).
[0017] Unless otherwise specified, the measured acid value is a value measured in accordance with "JIS (Japanese Industrial Standards) K0070-1992".
[0018] Unless otherwise specified, the "major component" of a material means the component that is contained in the largest amount in the material on a mass basis.
[0019] Hereinafter, the compound and its derivatives may be collectively referred to by adding "based" after the compound name. When the compound name is followed by "based" to represent the name of a polymer, it means that the repeating unit of the polymer is derived from the compound or its derivative.
[0020] <First embodiment: Toner> The first embodiment of the present invention relates to a toner. The toner of this embodiment includes toner particles. The toner particles include toner base particles and an external additive attached to the surface of the toner base particles. The number-average circularity of the toner base particles is 0.950 or more and 0.985 or less. The toner base particles contain a binder resin having a glass transition point of 20° C. or more and 65° C. or less and a positively charged charge control agent. The binder resin includes a specific styrene-(meth)acrylic resin. The content ratio of the specific styrene-(meth)acrylic resin in the toner base particles is 50.0% by mass or more and 95.0% by mass or less. The acid value of the specific styrene-(meth)acrylic resin is 2.5 mgKOH / g or more and 30.0 mgKOH / g or less.
[0021] The toner of the present embodiment can be suitably used for developing electrostatic latent images. The toner of the present embodiment may be used as a one-component developer. The toner of the present embodiment may be mixed with a carrier using a mixing device (e.g., a bowl mill) and used as a two-component developer. When used as a one-component developer, the toner of the present embodiment is charged (e.g., positively charged) by friction with a developing sleeve or a toner charging member in a developing device. An example of a toner charging member is a doctor blade. When used as a two-component developer, the toner of the present embodiment is charged (e.g., positively charged) by friction with a carrier in a developing device.
[0022] [Toner particles] FIG. 1 shows an example of a toner particle 1 contained in the toner of this embodiment. The toner particle 1 shown in FIG. 1 includes a toner base particle 10 and an external additive 13 attached to the surface of the toner base particle 10. The toner base particle 10 has a toner core 11 containing a binder resin and a shell layer 12 that covers the surface of the toner core 11. That is, the toner particle 1 is a capsule toner particle having the shell layer 12. The shell layer 12 contains a charge control agent. The shell layer 12 preferably contains hydrophobic resin particles and positively charged resin particles. In this case, the positively charged resin particles contain a charge control agent.
[0023] Toner particle 1, which is an example of a toner particle, has been described above with reference to Fig. 1. However, the toner particles contained in the toner of the present embodiment may have a structure different from that of toner particle 1 shown in Fig. 1. Specifically, the toner base particle may not have a shell layer. In other words, the toner particle may not be a capsule toner particle.
[0024] The toner of the present embodiment has the above-mentioned configuration, and is excellent in chargeability and can suppress the occurrence of cleaning failure. The reason why the toner of the present embodiment can exhibit the above-mentioned effects is presumed to be as follows. In the toner of the present embodiment, the toner base particles have a number-average circularity of 0.950 or more and 0.985 or less. Since the toner base particles are relatively close to a perfect sphere (number-average circularity of 0.950 or more), the toner particles can satisfy basic characteristics such as fluidity required for toner particles. In addition, since the toner base particles are not completely perfect spheres (number-average circularity of 0.985 or less), the toner particles have an appropriate friction force. Therefore, the toner particles do not slip through the mechanism for cleaning the residual toner present on the photosensitive drum (particularly, the cleaning blade), and can be easily cleaned. As a result, the toner of the present embodiment can suppress the occurrence of cleaning failure.
[0025] The toner base particles contain a specific styrene-(meth)acrylic resin having a relatively high acid value as a main component. The specific styrene-(meth)acrylic resin has a certain amount of acid groups in the molecule, and therefore imparts moderate hydrophilicity to the toner base particles. For this reason, in the manufacturing process of the toner of this embodiment, the toner base particles can be subjected to a dispersion treatment in which the toner base particles are dispersed in an aqueous medium. In the dispersion treatment, the number-average circularity of the toner base particles can be easily controlled by adjusting the treatment temperature. Specifically, the higher the treatment temperature, the softer the binder resin contained in the toner base particles becomes, and the toner base particles approach a perfect sphere due to the action of surface tension. In addition, the specific styrene-(meth)acrylic resin has a moderately low affinity with a positively charged charge control agent. Therefore, the charge control agent contained in the toner base particles tends to repel the specific styrene-(meth)acrylic resin and localize near the surface of the toner base particles. In this way, the toner of the present embodiment contains the specific styrene-(meth)acrylic resin, which makes it possible to easily control the number-average circularity of the toner base particles and localize the charge control agent near the surface of the toner base particles, and as a result, the toner of the present embodiment can exhibit excellent chargeability while suppressing the occurrence of cleaning defects.
[0026] The toner of the present embodiment will be described in further detail below. Each of the components described below may be used alone or in combination of two or more, unless otherwise specified.
[0027] [Toner particles] The toner particles include a toner base particle and an external additive attached to the surface of the toner base particle.
[0028] (Toner base particles) The toner base particles contain a binder resin and a positively charged charge control agent. The toner base particles may further contain an internal additive (for example, at least one of a colorant, a release agent, a charge control agent, and a magnetic powder) as necessary. Examples of the toner base particles include pulverized toner base particles obtained by a pulverization method and aggregated toner base particles obtained by an aggregation method, and pulverized toner base particles are preferred. From the viewpoint of forming a good image, the volume median diameter (D 50 ) is preferably 4 μm or more and 9 μm or less.
[0029] The number-average circularity of the toner base particles is 0.950 or more and 0.985 or less, and preferably 0.960 or more and 0.980 or less. By making the number-average circularity of the toner base particles 0.950 or more, the toner particles can be given sufficient fluidity. By making the number-average circularity of the toner base particles 0.985 or less, the toner of this embodiment can suppress the occurrence of cleaning defects. The number-average circularity of the toner base particles can be measured by the method described in the examples or a method based thereon.
[0030] (Toner core) The toner base particle has, for example, a toner core and a shell layer that covers the surface of the toner core. In this case, the toner core contains a binder resin. The toner core may further contain an internal additive (for example, at least one of a colorant, a release agent, and other components other than those described above) as necessary.
[0031] (Binding resin) The binder resin includes a specific styrene-(meth)acrylic resin. The binder resin may further include a resin other than the specific styrene-(meth)acrylic resin (hereinafter, may be referred to as another binder resin). Examples of the other binder resin include a styrene resin, an olefin resin (e.g., a polyethylene resin and a polypropylene resin), a vinyl resin (e.g., a vinyl chloride resin, a polyvinyl alcohol, a vinyl ether resin, and an N-vinyl resin), a polyester resin, a polyamide resin, and a urethane resin. It is preferable that the binder resin further includes a polyester resin as the other binder resin.
[0032] The glass transition point of the binder resin is 20°C or higher and 65°C or lower, preferably 30°C or higher and 60°C or lower, more preferably 40°C or higher and 60°C or lower, and even more preferably 45°C or higher and 55°C or lower.
[0033] The content of the binder resin in the toner base particles is preferably from 70.0% by mass to 92.0% by mass, and more preferably from 80.0% by mass to 92.0% by mass.
[0034] The content of the binder resin in the toner core is preferably from 75.0% by mass to 97.0% by mass, and more preferably from 85.0% by mass to 95.0% by mass.
[0035] (Specific styrene-(meth)acrylic resin) The acid value of the specific styrene-(meth)acrylic resin is from 2.5 mgKOH / g to 30.0 mgKOH / g, preferably from 4.5 mgKOH / g to 10.0 mgKOH / g, and more preferably from 6.0 mgKOH / g to 8.0 mgKOH / g. By setting the acid value of the specific styrene-(meth)acrylic resin to be from 2.5 mgKOH / g to 30.0 mgKOH / g, the chargeability of the toner of this embodiment can be optimized.
[0036] The specific styrene-(meth)acrylic resin has, for example, a repeating unit derived from a styrene compound, a repeating unit derived from (meth)acrylic acid, and a repeating unit derived from an alkyl (meth)acrylate.
[0037] Examples of the styrene compound include styrene, o-methylstyrene, m-methylstyrene, p-methylstyrene, p-phenylstyrene, p-ethylstyrene, 2,4-dimethylstyrene, p-tert-butylstyrene, pn-hexylstyrene, pn-octylstyrene, pn-nonylstyrene, pn-decylstyrene, and pn-dodecylstyrene. As the styrene compound, styrene is preferred.
[0038] Examples of (meth)acrylic acid alkyl esters include methyl (meth)acrylate, ethyl (meth)acrylate, n-propyl (meth)acrylate, isopropyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, tert-butyl (meth)acrylate, n-octyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, stearyl (meth)acrylate, and lauryl (meth)acrylate.
[0039] The glass transition point of the specific styrene-(meth)acrylic resin is preferably 30°C or higher and 60°C or lower, more preferably 40°C or higher and 60°C or lower, and even more preferably 45°C or higher and 55°C or lower.
[0040] The content of the specific styrene-(meth)acrylic resin in the toner base particles is preferably from 50.0% by mass to 95.0% by mass, more preferably from 55.0% by mass to 80.0% by mass, and even more preferably from 58.0% by mass to 69.0% by mass.
[0041] The content of the specific styrene-(meth)acrylic resin in the binder resin is preferably from 60.0% by mass to 100.0% by mass, and more preferably from 60.0% by mass to 80.0% by mass.
[0042] The content of the specific styrene-(meth)acrylic resin in the toner core is preferably from 52.0% by mass to 97.0% by mass, and more preferably from 60.0% by mass to 70.0% by mass.
[0043] (polyester resin) The polyester resin is obtained by polycondensation of one or more polyhydric alcohols and one or more polycarboxylic acids. Examples of the polyhydric alcohols for synthesizing the polyester resin include dihydric alcohols (e.g., diol compounds and bisphenol compounds) and trivalent or higher alcohols. Examples of the polycarboxylic acids for synthesizing the polyester resin include divalent carboxylic acids and trivalent or higher carboxylic acids. Instead of the polycarboxylic acids, polycarboxylic acid derivatives capable of forming ester bonds by polycondensation (e.g., polycarboxylic acid anhydrides and polycarboxylic acid halides) may be used. The polyester resin preferably has a bisphenol A skeleton.
[0044] Examples of diol compounds include ethylene glycol, diethylene glycol, triethylene glycol, 1,2-propanediol, 1,3-propanediol, 1,4-butanediol, neopentyl glycol, 2-butene-1,4-diol, 1,5-pentanediol, 2-pentene-1,5-diol, 1,6-hexanediol, 1,4-cyclohexanedimethanol, dipropylene glycol, 1,4-benzenediol, polyethylene glycol, polypropylene glycol, and polytetramethylene glycol.
[0045] Examples of bisphenol compounds include bisphenol A, hydrogenated bisphenol A, ethylene oxide adducts of bisphenol A (eg, polyoxyethylene(2,2)-2,2-bis(4-hydroxyphenyl)propane), and propylene oxide adducts of bisphenol A.
[0046] Examples of trihydric or higher alcohols include sorbitol, 1,2,3,6-hexanetetrol, 1,4-sorbitan, pentaerythritol, dipentaerythritol, tripentaerythritol, 1,2,4-butanetriol, 1,2,5-pentanetriol, glycerol, diglycerol, 2-methylpropanetriol, 2-methyl-1,2,4-butanetriol, trimethylolethane, trimethylolpropane, and 1,3,5-trihydroxymethylbenzene.
[0047] Examples of divalent carboxylic acids include maleic acid, fumaric acid, citraconic acid, itaconic acid, glutaconic acid, phthalic acid, isophthalic acid, terephthalic acid, cyclohexanedicarboxylic acid, adipic acid, sebacic acid, azelaic acid, malonic acid, succinic acid, alkylsuccinic acids (more specifically, n-butylsuccinic acid, isobutylsuccinic acid, n-octylsuccinic acid, n-dodecylsuccinic acid, isododecylsuccinic acid), and alkenylsuccinic acids (more specifically, n-butenylsuccinic acid, isobutenylsuccinic acid, n-octenylsuccinic acid, n-dodecenylsuccinic acid, isododecenylsuccinic acid).
[0048] Examples of trivalent or higher carboxylic acids include 1,2,4-benzenetricarboxylic acid (trimellitic acid), 2,5,7-naphthalenetricarboxylic acid, 1,2,4-naphthalenetricarboxylic acid, 1,2,4-butanetricarboxylic acid, 1,2,5-hexanetricarboxylic acid, 1,3-dicarboxyl-2-methyl-2-methylenecarboxylpropane, 1,2,4-cyclohexanetricarboxylic acid, tetra(methylenecarboxyl)methane, 1,2,7,8-octanetetracarboxylic acid, pyromellitic acid, and empol trimer acid.
[0049] The glass transition point of the polyester resin is preferably 30°C or higher and 60°C or lower, more preferably 40°C or higher and 60°C or lower, and even more preferably 45°C or higher and 55°C or lower.
[0050] The content of the polyester resin in the toner base particles is preferably from 4.0% by mass to 38.0% by mass, and more preferably from 18.0% by mass to 28.0% by mass.
[0051] The content of the polyester resin in the binder resin is preferably from 10.0% by mass to 40.0% by mass, and more preferably from 20.0% by mass to 30.0% by mass.
[0052] The content of the polyester resin in the toner core is preferably from 5.0% by mass to 40.0% by mass, and more preferably from 20.0% by mass to 30.0% by mass.
[0053] (Coloring agent) The toner base particles (for example, toner core) may contain a colorant. As the colorant, a known pigment or dye can be used in accordance with the color of the toner of the present embodiment. From the viewpoint of forming a high-quality image using the toner of the present embodiment, the content of the colorant in the toner base particles (for example, toner core) is preferably 1.0 parts by mass or more and 20.0 parts by mass or less, and more preferably 4.0 parts by mass or more and 7.0 parts by mass or less, relative to 100 parts by mass of the binder resin.
[0054] The toner base particles may contain a black colorant. An example of the black colorant is carbon black. The black colorant may be a colorant toned to black using a yellow colorant, a magenta colorant, and a cyan colorant.
[0055] The toner base particles may contain color colorants, including yellow, magenta, and cyan colorants.
[0056] As the yellow colorant, for example, one or more compounds selected from the group consisting of condensed azo compounds, isoindolinone compounds, anthraquinone compounds, azo metal complexes, methine compounds, and arylamide compounds can be used. As the yellow colorant, for example, CI Pigment Yellow (3, 12, 13, 14, 15, 17, 62, 74, 83, 93, 94, 95, 97, 109, 110, 111, 120, 127, 128, 129, 147, 151, 154, 155, 168, 174, 175, 176, 180, 181, 191, and 194), Naphthol Yellow S, Hansa Yellow G, and CI Vat Yellow can be mentioned.
[0057] As the magenta colorant, for example, one or more compounds selected from the group consisting of condensed azo compounds, diketopyrrolopyrrole compounds, anthraquinone compounds, quinacridone compounds, basic dye lake compounds, naphthol compounds, benzimidazolone compounds, thioindigo compounds, and perylene compounds can be used. As the magenta colorant, for example, CI Pigment Red (2, 3, 5, 6, 7, 19, 23, 48:2, 48:3, 48:4, 57:1, 81:1, 122, 144, 146, 150, 166, 169, 177, 184, 185, 202, 206, 220, 221, and 254) can be used.
[0058] As the cyan colorant, for example, one or more compounds selected from the group consisting of copper phthalocyanine compounds, anthraquinone compounds, and basic dye lake compounds can be used. As the cyan colorant, for example, CI Pigment Blue (1, 7, 15, 15:1, 15:2, 15:3, 15:4, 60, 62, and 66), phthalocyanine blue, CI Vat Blue, and CI Acid Blue can be used.
[0059] (Release agent) The toner mother particles (for example, toner core) may contain a release agent. The release agent is used, for example, for the purpose of imparting offset resistance to the toner of the present embodiment. From the viewpoint of imparting sufficient offset resistance to the toner of the present embodiment, the content of the release agent in the toner mother particles (for example, toner core) is preferably 1.0 parts by mass or more and 20.0 parts by mass or less, and more preferably 3.0 parts by mass or more and 8.0 parts by mass or less, relative to 100 parts by mass of the binder resin.
[0060] Examples of the release agent include aliphatic hydrocarbon waxes, oxides of aliphatic hydrocarbon waxes, vegetable waxes, animal waxes, mineral waxes, ester waxes mainly composed of fatty acid esters, and waxes in which a part or all of the fatty acid esters are deoxidized. Examples of the aliphatic hydrocarbon waxes include low molecular weight polyethylene, low molecular weight polypropylene, polyolefin copolymers, polyolefin waxes, microcrystalline waxes, paraffin waxes, and Fischer-Tropsch waxes. Examples of the oxides of aliphatic hydrocarbon waxes include oxidized polyethylene waxes and block copolymers of oxidized polyethylene waxes. Examples of the vegetable waxes include candelilla wax, carnauba wax, Japan wax, jojoba wax, and rice wax. Examples of the animal waxes include beeswax, lanolin, and spermaceti. Examples of the mineral waxes include ozokerite, ceresin, and petrolatum. Examples of the ester waxes mainly composed of fatty acid esters include montan acid ester wax and castor wax. An example of the wax in which the fatty acid ester is partially or completely deoxidized is deoxidized carnauba wax. As the release agent, an ester wax is preferable.
[0061] When the toner base particles contain a release agent, a compatibilizer may be added to the toner base particles (for example, toner core) in order to improve the compatibility between the binder resin and the release agent.
[0062] (Shell layer) The shell layer contains a positively charged charge control agent. The shell layer preferably contains hydrophobic resin particles and positively charged resin particles. In this case, the positively charged resin particles contain a charge control agent. In this way, by including the charge control agent in the shell layer, the charge control agent can be reliably localized near the surface of the toner base particle. As a result, the toner of this embodiment can exhibit even better charging properties. The total content ratio of the hydrophobic resin particles and the positively charged resin particles in the shell layer is preferably 70% by mass or more, more preferably 90% by mass or more, and even more preferably 100% by mass.
[0063] (Charge control agent) The charge control agent is used, for example, for the purpose of providing a toner having excellent charge stability or charge rise property. The charge rise property of a toner is an index of whether or not the toner can be charged to a predetermined charge level in a short time. By incorporating a positively chargeable charge control agent in the toner base particles, the cationic nature of the toner base particles can be enhanced.
[0064] Examples of the positively charged charge control agent include azine compounds, direct dyes, acid dyes, alkoxylated amines, alkylamides, quaternary ammonium salt compounds, and resins containing quaternary ammonium cationic groups. As the charge control agent, resins containing quaternary ammonium cationic groups are preferred.
[0065] Examples of the azine compound include pyridazine, pyrimidine, pyrazine, 1,2-oxazine, 1,3-oxazine, 1,4-oxazine, 1,2-thiazine, 1,3-thiazine, 1,4-thiazine, 1,2,3-triazine, 1,2,4-triazine, 1,3,5-triazine, 1,2,4-oxadiazine, 1,3,4-oxadiazine, 1,2,6-oxadiazine, 1,3,4-thiadiazine, 1,3,5-thiadiazine, 1,2,3,4-tetrazine, 1,2,4,5-tetrazine, 1,2,3,5-tetrazine, 1,2,4,6-oxatriazine, 1,3,4,5-oxatriazine, phthalazine, quinazoline, and quinoxaline.
[0066] Examples of direct dyes include Azin Fast Red FC, Azin Fast Red 12BK, Azin Violet BO, Azin Brown 3G, Azin Light Brown GR, Azin Dark Green BH / C, Azin Deep Black EW, and Azin Deep Black 3RL.
[0067] Acid dyes include, for example, Nigrosine BK, Nigrosine NB, and Nigrosine Z.
[0068] Examples of quaternary ammonium salt compounds include benzyldecylhexylmethylammonium chloride, decyltrimethylammonium chloride, 2-(methacryloyloxy)ethyltrimethylammonium chloride, and dimethylaminopropylacrylamide methyl chloride quaternary salt.
[0069] In the resin containing a quaternary ammonium cationic group, the quaternary ammonium cationic group may, for example, be a trialkylammonium cationic group (e.g., a trimethylammonium cationic group and a triethylammonium cationic group). Note that, as the counter anion of the quaternary ammonium cationic group, for example, a halogen ion (e.g., Cl - ) can be mentioned. The resin containing a quaternary ammonium cationic group has, for example, a repeating unit (hereinafter, sometimes referred to as a specific repeating unit) derived from a vinyl monomer having a trialkylammonium cationic group. A specific example of the above-mentioned vinyl monomer is 2-(methacryloyloxy)ethyltrimethylammonium chloride.
[0070] The resin containing a quaternary ammonium cationic group preferably further has a repeating unit derived from a (meth)acrylic acid alkyl ester in addition to the specific repeating unit. The (meth)acrylic acid alkyl ester may be, for example, the same as the (meth)acrylic acid alkyl ester exemplified in the specific styrene-(meth)acrylic resin. In the resin containing a quaternary ammonium cationic group, the (meth)acrylic acid alkyl ester is preferably methyl methacrylate or butyl acrylate.
[0071] The resin containing a quaternary ammonium cationic group is preferably a resin having a specific repeating unit, a repeating unit derived from methyl methacrylate, and a repeating unit derived from butyl acrylate. In this case, the content ratio of the specific repeating unit is preferably 5.0% by mass or more and 30.0% by mass or less, more preferably 12.0% by mass or more and 25.0% by mass or less, based on the total repeating units of the resin containing a quaternary ammonium cationic group. Similarly, the content ratio of the repeating unit derived from methyl methacrylate is preferably 40.0% by mass or more and 80.0% by mass or less, more preferably 55.0% by mass or more and 65.0% by mass or less. Similarly, the content ratio of the repeating unit derived from butyl acrylate is preferably 5.0% by mass or more and 35.0% by mass or less, more preferably 15.0% by mass or more and 25.0% by mass or less.
[0072] From the viewpoint of providing a toner having excellent charging stability, the content of the charge control agent in the toner base particles is preferably 0.05 parts by mass or more and 3.0 parts by mass or less, and more preferably 0.1 parts by mass or more and 0.4 parts by mass or less, relative to 100 parts by mass of the binder resin.
[0073] (Positively charged resin particles) The positively charged resin particles contain the charge control agent described above. The number average primary particle diameter of the positively charged resin particles is preferably 15 nm or more and 100 nm or less, and more preferably 25 nm or more and 50 nm or less.
[0074] The positively charged resin particles preferably contain a resin containing a quaternary ammonium cationic group, and preferably contain only a resin containing a quaternary ammonium cationic group. The content of the resin containing a quaternary ammonium cationic group in the positively charged resin particles is preferably 70% by mass or more, more preferably 90% by mass or more, and even more preferably 100% by mass.
[0075] In the toner base particles, the content of the positively charged resin particles is preferably 0.05 parts by mass to 3.0 parts by mass, more preferably 0.1 parts by mass to 0.5 parts by mass, relative to 100 parts by mass of the toner core. By setting the content of the positively charged resin particles to 0.05 parts by mass to 3.0 parts by mass, the toner of this embodiment can exhibit even better charging properties.
[0076] (Hydrophobic resin particles) The hydrophobic resin particles further optimize the flowability of the toner of the present embodiment. The hydrophobic resin particles contain a hydrophobic resin. The content of the hydrophobic resin in the hydrophobic resin particles is preferably 70% by mass or more, more preferably 90% by mass or more, and even more preferably 100% by mass.
[0077] Examples of hydrophobic resins include styrene-(meth)acrylic resins, and copolymers of styrene and (meth)acrylic acid alkyl esters are preferred, with copolymers of styrene and butyl acrylate being more preferred. In the copolymers of styrene and (meth)acrylic acid alkyl esters, the content of repeating units derived from styrene is preferably 70% by mass or more and 98% by mass or less, more preferably 80% by mass or more and 95% by mass or less. In the copolymers of styrene and (meth)acrylic acid alkyl esters, the content of repeating units derived from (meth)acrylic acid alkyl esters is preferably 2% by mass or more and 30% by mass or less, more preferably 5% by mass or more and 20% by mass or less.
[0078] The glass transition point of the hydrophobic resin is preferably from 70° C. to 90° C., more preferably from 70° C. to 80° C. The acid value of the hydrophobic resin is preferably from 1.0 mgKOH / g to 0.3 mgKOH / g or less, more preferably from 0.3 mgKOH / g to 0.3 mgKOH / g or less.
[0079] The number average primary particle diameter of the hydrophobic resin particles is preferably 10 nm or more and 100 nm or less, and more preferably 20 nm or more and 45 nm or less.
[0080] In the toner base particles, the content of the hydrophobic resin particles is preferably 0.5 parts by mass to 5.0 parts by mass, more preferably 1.0 parts by mass to 3.0 parts by mass, relative to 100 parts by mass of the toner core. By setting the content of the hydrophobic resin particles to 0.5 parts by mass to 5.0 parts by mass, the toner of this embodiment can exhibit even better fluidity.
[0081] (External additives) As the external additive, inorganic particles are preferred. As the inorganic particles, silica particles or metal oxide particles (more specifically, alumina, titanium oxide, magnesium oxide, zinc oxide, strontium titanate, barium titanate, etc.) are preferred, and silica particles or titanium oxide particles are more preferred. The number average primary particle diameter of the silica particles is preferably 5 nm or more and 200 nm or less, more preferably 10 nm or more and 40 nm or less. The number average primary particle diameter of the titanium oxide particles is preferably 50 nm or more and 600 nm or less, more preferably 300 nm or more and 450 nm or less.
[0082] The content of the external additive in the toner particles is preferably 0.1 parts by mass or more and 15.0 parts by mass or less, and more preferably 2.5 parts by mass or more and 5.0 parts by mass or less, relative to 100 parts by mass of the toner base particles, from the viewpoint of fully exerting its function while suppressing detachment from the toner base particles.
[0083] The content of the silica particles in the toner particles is preferably from 0.5 to 5.0 parts by mass, more preferably from 1.5 to 2.5 parts by mass, and the content of the titanium oxide particles in the toner particles is preferably from 0.3 to 3.0 parts by mass, more preferably from 1.0 to 2.0 parts by mass.
[0084] <Second embodiment: Toner manufacturing method> The second embodiment of the present invention relates to a method for producing a toner. The method for producing a toner according to the present embodiment is a method for producing a toner containing toner particles, and includes a toner core preparation step of preparing a toner core containing a binder resin, a shell layer formation step of obtaining toner base particles by forming a shell layer on the surface of the toner core, and an external addition step of obtaining toner particles by attaching an external additive to the surface of the toner base particles. The glass transition point of the binder resin is 20° C. or higher and 65° C. or lower. The binder resin includes a specific styrene-(meth)acrylic resin. The content ratio of the specific styrene-(meth)acrylic resin in the toner base particles is 50.0% by mass or higher and 95.0% by mass or lower. The acid value of the specific styrene-(meth)acrylic resin is 2.5 mgKOH / g or higher and 30.0 mgKOH / g or lower. The shell layer includes hydrophobic resin particles and positively charged resin particles. In the shell layer formation step, the toner core, the hydrophobic resin particles, and the positively charged resin particles are dispersed at a processing temperature of 55° C. or higher and 78° C. or lower. The toner manufacturing method of the present embodiment is suitable as the toner manufacturing method of the first embodiment. The toner obtained by the toner manufacturing method of the present embodiment has excellent chargeability and can suppress the occurrence of cleaning defects. In addition, the toner manufacturing method of the present embodiment can produce the toner without using an organic solvent, so that the manufacturing cost and the environmental load can be reduced.
[0085] In the toner production method of the present embodiment, the details of each component contained in the toner are the same as those in the first embodiment, so that a duplicated description will be omitted.
[0086] (Toner core preparation process) In this process, the toner cores are prepared, for example, by a pulverization method. The toner core preparation process includes, for example, a melt-kneading process and a pulverization process. This process may further include a mixing process before the melt-kneading process. In addition, this process may further include at least one of a fine pulverization process and a classification process after the pulverization process.
[0087] In the mixing step, the binder resin and the internal additives added as necessary are mixed to obtain a mixture. In the melting and kneading step, the toner materials are melted and kneaded to obtain a melted and kneaded product. For example, the mixture obtained in the mixing step is used as the toner material. In the pulverizing step, the obtained melted and kneaded product is cooled, for example, to room temperature (25°C), and then pulverized to obtain a pulverized product. If it is necessary to reduce the diameter of the pulverized product obtained in the pulverizing step, a step of further pulverizing the pulverized product (fine pulverizing step) may be performed. Furthermore, if the particle size of the pulverized product is to be uniform, a step of classifying the obtained pulverized product (classifying step) may be performed. Through the above steps, a toner core, which is a pulverized product, is obtained.
[0088] (Shell layer formation process) In this process, a shell layer is formed on the surface of the toner core to obtain the toner base particles. Specifically, the toner core, the hydrophobic resin particles, and the positively charged resin particles are dispersed at a predetermined processing temperature. As a result, the hydrophobic resin particles and the positively charged resin particles adhere to the surface of the toner core to form a shell layer.
[0089] In the dispersion treatment, the treatment temperature is 55° C. to 78° C., and preferably 65° C. to 72° C. In this process, the binder resin can be appropriately softened by forming the toner base particles while heating at a treatment temperature of 55° C. to 78° C. As a result, the formed toner base particles can be given an appropriate number average circularity.
[0090] The stirring speed in the dispersion treatment is preferably 30 rpm or more and 300 rpm or less. The treatment time in the dispersion treatment (the time for stirring the dispersion at the above treatment temperature) is preferably 10 minutes or more and 60 minutes or less. The dispersion treatment is preferably carried out in a dispersion liquid under acidic conditions (e.g., pH 3 to 5). After the dispersion treatment, it is preferable to return the dispersion liquid to neutral conditions (e.g., pH 6 to 8).
[0091] The hydrophobic resin particles have the role of suppressing the aggregation of the toner base particles in this process. On the other hand, even if an excessive amount of hydrophobic resin particles is used, they are not incorporated into the toner base particles and remain in the dispersion liquid. Therefore, the amount of the hydrophobic resin particles used in this process is preferably 0.5 parts by mass to 5.0 parts by mass, more preferably 1.0 parts by mass to 3.0 parts by mass, relative to 100 parts by mass of the toner core. The amount of the positively charged resin particles used is preferably 0.05 parts by mass to 3.0 parts by mass, more preferably 0.1 parts by mass to 0.5 parts by mass, relative to 100 parts by mass of the toner core.
[0092] The toner base particles obtained in this step are preferably thoroughly washed with ion-exchanged water or the like, and then dried before being subjected to the next external addition step.
[0093] (External addition process) In the external addition step, the above-mentioned toner base particles and the external additive are mixed using a mixer, and the external additive is attached to the surface of the toner base particles. This results in a toner. The external additive includes specific external additive particles and other external additive particles that are used as necessary. As an example of the mixer, an FM mixer (manufactured by Nippon Coke & Engineering Co., Ltd.) can be mentioned. EXAMPLES
[0094] The present invention will be described in more detail below using examples, but the present invention is not limited to the scope of the examples.
[0095] [Volume median diameter measurement] Volume median diameter of toner particles (D 50) was measured using a particle size meter (Beckman Coulter, Inc., Coulter Counter Multisizer 3).
[0096] [Measurement of glass transition temperature] A differential scanning calorimeter (Seiko Instruments Inc.'s "DSC-6220") was used as the measuring device. The endothermic curve of the sample was measured using the measuring device to determine the Tg (glass transition point) of the sample. Specifically, about 10 mg of the sample (e.g., resin) was placed in an aluminum dish (aluminum container), and the aluminum dish was set in the measuring section of the measuring device. An empty aluminum dish was also used as a reference.
[0097] In the measurement of the endothermic curve, the temperature of the measurement section was raised from the measurement start temperature of 25°C to 200°C at a rate of 10°C / min (RUN1). Then, the temperature of the measurement section was lowered from 200°C to 25°C at a rate of 10°C / min. Next, the temperature of the measurement section was raised again from 25°C to 200°C at a rate of 10°C / min (RUN2). The endothermic curve of the sample (vertical axis: heat flow (DSC signal), horizontal axis: temperature) was obtained by RUN2. The Tg of the sample was read from the obtained endothermic curve. In the endothermic curve, the temperature (onset temperature) of the change point of the specific heat (intersection of the extrapolated line of the baseline and the extrapolated line of the falling line) corresponds to the Tg (glass transition point) of the sample.
[0098] [Binding resin] As the resins used as the binder resins, styrene-acrylic resins (SA-1) to (SA-6) and polyester resins (PEs-1) to (PEs-2) shown in Table 1 were prepared. In Table 1, "Tg" indicates the glass transition point. The polyester resins (PEs-1) to (PEs-2) had a bisphenol A skeleton.
[0099] [Table 1]
[0100] [Preparation of shell layer material] Hydrophobic resin particles and positively charged resin particles to be used for forming the shell layer were prepared by the following method.
[0101] (Hydrophobic resin particles) A 1L three-neck flask equipped with a thermometer and a stirring blade was set in a water bath. 875mL of ion-exchanged water and 75mL of an anionic surfactant ("Latemul (registered trademark) WX" manufactured by Kao Corporation, component: polyoxyethylene alkyl ether sodium sulfate, solid content concentration: 26% by mass) were placed in the flask. Next, the internal temperature of the flask was raised to 80°C, and then the internal temperature of the flask was maintained at 80°C. Separately, 18mL of styrene and 2mL of butyl acrylate were mixed to prepare a first liquid. In addition, 0.5g of potassium persulfate was dissolved in 30g of ion-exchanged water to obtain a second liquid. The first and second liquids were each dropped into the above-mentioned flask over a period of 5 hours. Subsequently, the contents of the flask were polymerized by stirring the contents of the flask at a rotation speed of 250 rpm for 2 hours while maintaining the temperature in the flask at 80°C. As a result, a suspension containing hydrophobic resin particles composed of a copolymer of styrene and n-butyl acrylate (hydrophobic resin) (hereinafter, sometimes referred to as hydrophobic resin particle suspension) was obtained (solid content concentration 20 mass%). The hydrophobic resin particles in the hydrophobic resin particle suspension had a number average primary particle diameter of 32 nm. The glass transition point of the hydrophobic resin contained in the hydrophobic resin particles was 71°C.
[0102] (Positively charged resin particles) In a 1L three-neck flask equipped with a thermometer, a cooling tube, a nitrogen inlet tube, and a stirring blade, 90g of isobutanol, 100g of methyl methacrylate, 35g of butyl acrylate, 30g of 2-(methacryloyloxy)ethyl trimethylammonium chloride (manufactured by Alfa Aesar), and 6g of 2,2'-azobis[2-methyl-N-(2-hydroxyethyl)propionamide] (manufactured by Wako Pure Chemical Industries, Ltd., "VA-086") were placed. The contents of the flask were then reacted for 3 hours under a nitrogen atmosphere while maintaining the temperature in the flask at 80°C. Next, 3g of 2,2'-azobis[2-methyl-N-(2-hydroxyethyl)propionamide] (manufactured by Wako Pure Chemical Industries, Ltd., "VA-086") was added to the flask. Next, the contents of the flask were reacted for another 3 hours under a nitrogen atmosphere while maintaining the temperature in the flask at 80°C. This resulted in a polymer solution. The obtained polymer solution was dried under conditions of a temperature of 150° C. and a pressure of 0.1 kPa. As a result, a dried polymer was obtained. Next, the dried polymer was crushed to obtain a positively charged resin.
[0103] Next, 200 g of the above-mentioned positively charged resin and 184 mL of ethyl acetate (Wako Pure Chemical Industries, Ltd.'s "Ethyl acetate special grade") were placed in the container of a mixing device (PRIMIX Corporation's "Hibismix (registered trademark) 2P-1 type"). The contents of the container were then stirred for 1 hour at a rotation speed of 20 rpm to obtain a highly viscous uniform solution I. Separately, 18 mL of 1N hydrochloric acid, 20 g of an anionic surfactant (Kao Corporation's "Emal (registered trademark) 0", component: sodium lauryl sulfate), and 16 g of ethyl acetate (Wako Pure Chemical Industries, Ltd.'s "Ethyl acetate special grade") were dissolved in 562 mL of ion-exchanged water to prepare an aqueous solution II. Then, the above-mentioned aqueous solution II was added to the above-mentioned solution I. As a result, a suspension containing positively charged resin particles (thermoplastic resin containing quaternary ammonium cationic groups) (hereinafter referred to as a positively charged resin particle suspension) was obtained (solid content concentration 20 mass%). The resin particles contained in the positively charged resin particle suspension had a number average primary particle diameter of 35 nm.
[0104] <Toner Preparation> The toners of Examples 1 to 15 and Comparative Examples 1 to 7 were prepared by the following method.
[0105] [Example 1] (Toner core preparation process) Using an FM mixer ("FM-20B" manufactured by Nippon Coke & Engineering Co., Ltd.), 65.0 parts by mass of styrene-acrylic resin (SA-1) (low viscosity styrene-acrylic resin, glass transition point: 48°C, acid value 7.1 mgKOH / g), 25.0 parts by mass of polyester resin (PEs-1) (high viscosity polyester resin, glass transition point: 58°C, acid value 0.2 mgKOH / g), 5.0 parts by mass of ester wax ("Nissan Electol (registered trademark) WEP-3" manufactured by NOF Corporation, melting point: 73°C) as a release agent, and 5.0 parts by mass of phthalocyanine blue ("KET Blue111" manufactured by DIC Corporation) as a colorant were thoroughly mixed at a rotation speed of 2400 rpm.
[0106] The mixture was then melt-kneaded using a twin-screw extruder ("PCM-30" manufactured by Ikegai Corporation) under conditions of a material supply rate of 5 kg / hour, an axis rotation speed of 160 rpm, and a cylinder temperature of 100°C. The kneaded mixture was then cooled. The kneaded mixture was coarsely pulverized using a Rotoplex mill ("8 / 16" manufactured by Toa Kikai Seisakusho Co., Ltd.), and then finely pulverized using a supersonic jet pulverizer ("Ultrasonic Jet Mill I" manufactured by Nippon Pneumatic Mfg. Co., Ltd.). The finely pulverized product was classified using a classifier ("EJ-LABO Model EJ-L-3" manufactured by Nittetsu Mining Co., Ltd.). This resulted in the production of toner cores.
[0107] (Shell layer formation process) A 1L three-neck flask equipped with a thermometer and a stirring blade was set in a water bath, and 100 mL of ion-exchanged water was placed in the flask. After that, the temperature in the flask was kept at 30° C. using the water bath. Next, dilute hydrochloric acid was added to the flask to adjust the pH of the flask contents to 4. Next, 300 g of toner cores, 250 mL of hydrophobic resin particle suspension (hydrophobic resin particles: about 5 g), and 2.5 mL of positively charged resin particle suspension (positively charged resin particles: about 0.5 g) were added to the flask. Next, the flask contents were stirred for 1 hour at a rotation speed of 200 rpm. Next, 300 mL of ion-exchanged water was added to the flask. Next, while stirring the flask contents at a rotation speed of 100 rpm, the temperature in the flask was raised to 70° C. at a rate of 1° C. / min (hereinafter, the temperature in the flask after the temperature increase may be referred to as the "heating temperature T"). Next, the flask contents were stirred for 30 minutes under the conditions of heating temperature T (70° C.) and rotation speed of 100 rpm. Sodium hydroxide was then added to the flask to adjust the pH of the flask content to 7. The flask content was then cooled to a temperature of 25° C. This resulted in a dispersion liquid containing toner mother particles (particles having a toner core and a shell layer covering the surface of the toner core).
[0108] Assuming that the total amount of positively charged resin particles and hydrophobic resin particles are incorporated into the toner base particles, the content of each component in the toner base particles is 63.8% by mass of styrene-acrylic resin (SA-1), 24.5% by mass of polyester resin (PEs-1), 4.9% by mass of colorant and release agent, 0.2% by mass of positively charged resin particles, and 1.6% by mass of hydrophobic resin particles. In Table 3, the types of resins contained in the toner base particles at 50.0% or more by mass are shown as "resins at 50.0% or more by mass."
[0109] (Cleaning process) The resulting dispersion of toner base particles was then filtered (solid-liquid separation) using a Buchner funnel to obtain wet cake-like toner base particles. The resulting wet cake-like toner base particles were then redispersed in ion-exchanged water and filtered using a Buchner funnel. This redispersion and filtration were performed a total of five times each to wash the toner base particles. This resulted in the production of washed toner base particles.
[0110] (drying process) Next, the washed toner base particles were dispersed in an aqueous ethanol solution with a concentration of 50% by mass. This resulted in a slurry of toner base particles. Next, using a continuous surface modification device ("Coatmizer (registered trademark)" manufactured by Freund Corporation), the toner base particles were dispersed in a hot air temperature of 45°C and a blower volume of 2 m 3 The toner base particles in the slurry were dried under conditions of 0.1 ml / min. As a result, a powder of toner base particles (volume median diameter 6.86 μm) was obtained. When the surface of the toner base particles was observed with a scanning electron microscope, it was confirmed that a shell layer was formed by resin particles (hydrophobic resin particles or positively charged resin particles). In addition, when observed with the scanning electron microscope, it was not confirmed that the resin particles were separated from the shell layer.
[0111] (Measurement of number-average circularity) A surfactant ("Contaminon (registered trademark) n" manufactured by Wako Pure Chemical Industries, Ltd.) was diluted three times by mass with ion-exchanged water to obtain a surfactant dilution solution. 0.2 mL of the surfactant dilution solution, 20 mL of ion-exchanged water, and 0.02 g of toner base particles were placed in a container. While cooling the container contents to a temperature of 25°C ± 15°C, the container contents were subjected to a dispersion treatment for 2 minutes using an ultrasonic cleaner (oscillation frequency: 50 kHz, high-frequency output: 150 W) to obtain a toner base particle dispersion solution. The toner base particle dispersion solution was used as a measurement sample for number-average circularity.
[0112] Using a flow type particle image analyzer (Sysmex Corporation's "FPIA (registered trademark) 3000") equipped with a standard objective lens (magnification: 10x), the circularity measurement sample was measured under the following conditions to determine the number average circularity of the toner base particles. The measurement results are shown in Table 3. Measurement mode: HPF measurement mode and total count mode -Binarization threshold for particle analysis: 85% Analyzed particle size: Circle equivalent diameter of 20 μm or less
[0113] (Measurement of chargeability of toner base particles) A sample for evaluation was prepared by mixing 100 parts by mass of a ferrite carrier (carrier for "TASKalfa (registered trademark) 7054ci" manufactured by Kyocera Document Solutions Inc.) and 8 parts by mass of toner base particles to be used for evaluation for 30 minutes using a rocking mixer (registered trademark). The evaluation sample was placed in a measurement cell of a Q / m meter ("MODEL 210HS" manufactured by Trek). Using the Q / m meter, the charge amount [μC / g] of the toner base particles was measured while only the toner base particles of the evaluation sample were sucked through a sieve (wire mesh) for 10 seconds. The obtained charge amount was used as an evaluation value of the chargeability of the toner base particles. The measurement results are shown in Table 3.
[0114] (External addition process) 100.0 parts by mass of the above-mentioned toner base particles, 2.0 parts by mass of hydrophobic silica particles ("AEROSIL (registered trademark) RA-200H" manufactured by Nippon Aerosil Co., Ltd., number average primary particle diameter: 12 nm) as an external additive, and 1.5 parts by mass of titanium oxide particles ("EC-100" manufactured by Titanium Kogyo Co., Ltd.) were mixed using an FM mixer ("FM-10" manufactured by Nippon Coke and Engineering Co., Ltd.) at a rotation speed of 3000 rpm and a jacket control temperature of 20°C for 5 minutes to obtain a mixture. Then, the above-mentioned mixture was sieved using the obtained 200 mesh (opening 75 μm). As a result, the toner of Example 1 was obtained.
[0115] [Examples 2 to 13, Comparative Examples 1 to 7] The toners of Examples 2 to 13 and Comparative Examples 1 to 7 were obtained in the same manner as in the production of the toner of Example 1, except that the type and amount of resin used in the toner core preparation step and the heating temperature T in the shell layer formation step were changed as shown in Table 2. In the production of the toner of Example 13, no polyester resin was used in the toner core preparation step.
[0116] [Example 14] The toner of Example 14 was obtained in the same manner as in the production of the toner of Example 2, except for the following changes. In the production of the toner of Example 14, the amount of the hydrophobic resin particle suspension used in the shell layer forming step was changed to 125 mL (hydrophobic resin particles: about 2.5 g). In addition, in the production of the toner of Example 14, the amount of the positively charged resin particle suspension used in the shell layer forming step was changed to 5.0 mL (positively charged resin particles: about 1.0 g).
[0117] [Example 15] The toner of Example 15 was obtained in the same manner as in the toner of Example 1, except for the following changes. In the production of the toner of Example 15, the amount of the hydrophobic resin particle suspension used in the shell layer forming step was changed to 500 mL (hydrophobic resin particles: about 10 g). In addition, in the production of the toner of Example 15, the amount of the positively charged resin particle suspension used in the shell layer forming step was changed to 1.5 mL (positively charged resin particles: about 0.3 g).
[0118] In Table 2, "wt %" indicates the proportion [mass %] of the amount of each resin used in the toner core preparation process.
[0119] [Table 2]
[0120] <Evaluation> The toners of Examples 1 to 15 and Comparative Examples 1 to 7 were evaluated for chargeability and whether or not cleaning defects were suppressed by the following method. The evaluations were performed under conditions of a temperature of 23°C and a humidity of 50%, unless otherwise specified. The evaluation results are shown in Table 3. Table 3 shows the type and acid value of the resin contained in the toner base particles of each toner, the content of which is 50.0% by mass or more.
[0121] [Electrostatic property] The chargeability of the toner was evaluated based on the charge amount of the toner base particles measured in the "measurement of chargeability of toner base particles" performed during the production of each toner. Specifically, the chargeability of each toner was evaluated according to the following criteria.
[0122] (Standard for electrostatic charge) A (good): The charge amount of the toner base particles is 5.0 μC / g or more. B (poor): The charge amount of the toner base particles is less than 5.0 μC / g.
[0123] [Prevention of cleaning defects] A two-component developer containing the toner to be evaluated was prepared by the following method. First, 8 parts by mass of the toner to be evaluated and 100 parts by mass of the carrier (carrier for "FS-C5250DN" manufactured by Kyocera Document Solutions Inc.) were mixed for 30 minutes using a powder mixer ("Rocking Mixer (registered trademark)" manufactured by Aichi Electric Co., Ltd., mixing method: container rotation and rocking method). This resulted in a developer for evaluation containing the toner to be evaluated (toner concentration of about 7% by mass).
[0124] (Evaluation unit) A color multifunction printer ("FS-C5250DN" manufactured by Kyocera Document Solutions Inc.) was used as the evaluation machine. The evaluation machine was equipped with a developing device having at least a photosensitive drum and a cleaning blade for cleaning the photosensitive drum. The evaluation developer was placed in the developing device (specifically, the cyan developing device) of the evaluation machine. In addition, a refill toner (any of the toners of Examples 1 to 15 and Comparative Examples 1 to 7) was placed in the cyan toner container of the evaluation machine.
[0125] Using the evaluation machine, a rectangular solid image was formed on A4 size printing paper. When forming the solid image, the vertical axis (longitudinal axis) of the solid image was set to coincide with the vertical axis of the printing paper. The center of the solid image was also set to coincide with the center of the printing paper. Furthermore, the size of the solid image was set to a width of 30 mm and a length to the maximum length that can be printed on the printing paper. Immediately after the solid image was formed on the printing paper, the power supply to the main body of the evaluation machine was cut off. Then, the photoconductor drum was removed from the evaluation machine.
[0126] When forming the above-mentioned solid image, an electrostatic latent image corresponding to the solid image was formed on the above-mentioned photosensitive drum. Next, the electrostatic latent image formed on the photosensitive drum was developed by a developing device. As a result, a toner image was formed on the photosensitive drum. Next, the toner image formed on the photosensitive drum was transferred to a printing paper. As a result, the toner image was removed from the photosensitive drum. However, residual toner was present in the area of the photosensitive drum where the toner image was formed (hereinafter, sometimes referred to as the "toner image area"). Next, the toner image area of the photosensitive drum was cleaned by a cleaning blade. Immediately after this, the power supply to the main body of the above-mentioned evaluation machine was cut off. In other words, the photosensitive drum removed from the evaluation machine was in a state immediately after the toner image area was cleaned.
[0127] After cellophane tape (hereinafter sometimes referred to as cellophane tape A) was attached to the toner image area of the photosensitive drum, the cellophane tape A was peeled off. As a result, the entire amount of residual toner (residual toner not removed even by cleaning with a cleaning blade) that existed in the toner image area of the photosensitive drum was adsorbed onto the cellophane tape A. Then, the cellophane tape A was attached to a new printing paper. In addition, a new cellophane tape (hereinafter sometimes referred to as cellophane tape B) was attached to the margin of the printing paper to measure the background value. This printing paper was used as a measurement sample. In the measurement sample, the image density X of the area where the cellophane tape A was attached and the image density Y of the area where the cellophane tape B was attached were measured using a reflection densitometer (X-Rite "RD914"). The image density X was the total value of the image density due to the cellophane tape A itself, the image density due to the residual toner adsorbed to the cellophane tape A, and the image density due to the printing paper itself. Image density Y was the sum of the image density caused by the cellophane tape B itself and the image density caused by the printing paper itself. The value obtained by subtracting image density Y from image density X (i.e., the image density caused by residual toner) was used as the evaluation value for suppression of cleaning defects (evaluation value = image density X - image density Y). The presence or absence of suppression of cleaning defects was judged according to the following criteria.
[0128] (Criteria for suppressing cleaning defects) A (good): Evaluation value is 0.010 or less. B (Poor): Evaluation value is greater than 0.010.
[0129] [Table 3]
[0130] The toners of Examples 1 to 15 contained toner particles. The toner particles included toner base particles and an external additive attached to the surface of the toner base particles. The number average circularity of the toner base particles was 0.950 or more and 0.985 or less. The toner base particles contained a binder resin having a glass transition point of 20° C. or more and 65° C. or less, and a positively charged charge control agent. The binder resin contained a specific styrene-(meth)acrylic resin. The content ratio of the specific styrene-(meth)acrylic resin in the toner base particles was 50.0 mass % or more and 95.0 mass % or less. The acid value of the specific styrene-(meth)acrylic resin was 2.5 mgKOH / g or more and 30.0 mgKOH / g or less. The chargeability was excellent and the occurrence of cleaning defects could be suppressed.
[0131] In contrast, in the toners of Comparative Examples 1 to 4, the acid value of the resin contained in the toner base particles at 50.0% by mass or more was less than 2.5 mgKOH / g. In the toner of Comparative Example 7, the resin contained in the toner base particles at 50.0% by mass or more was a polyester resin. It is considered that the toners of Comparative Examples 1 to 4 and 7 did not have a positively charged charge control agent localized on the surface of the toner base particles. As a result, the toners of Comparative Examples 1 to 4 and 7 had insufficient chargeability.
[0132] The toners of Comparative Examples 5 to 6 had a number-average circularity of the toner base particles exceeding 0.985. The toners of Comparative Examples 5 to 6 had a shape close to a perfect sphere, so that the toner particles were likely to slip through the gap between the photoconductor drum and the cleaning blade during cleaning of the photoconductor drum. Therefore, the toners of Comparative Examples 5 to 6 caused poor cleaning. In addition, the toner of Comparative Example 6 had an acid value of less than 2.5 mgKOH / g of the resin contained in the toner base particles at 50.0% by mass or more. As a result, the toner of Comparative Example 6 also had insufficient charging properties. [Industrial Applicability]
[0133] The toner of the present embodiment and the toner obtained by the method for producing a toner of the present embodiment can be used to form an image in, for example, a copier, a printer, or a multifunction machine. [Explanation of symbols]
[0134] 1 Toner particles 10 Toner base particles 11 Toner Core 12 Shell Layer 13 External additives
Claims
1. A toner comprising toner particles, The toner particles include a toner base particle and an external additive attached to a surface of the toner base particle, the number average circularity of the toner base particles is 0.950 or more and 0.985 or less; the toner base particles contain a binder resin having a glass transition point of 20° C. or more and 65° C. or less, and a positively charged charge control agent; The binder resin contains a specific styrene-(meth)acrylic resin, the content of the specific styrene-(meth)acrylic resin in the toner base particles is 50.0% by mass or more and 95.0% by mass or less, The toner, wherein the specific styrene-(meth)acrylic resin has an acid value of 2.5 mgKOH / g or more and 30.0 mgKOH / g or less.
2. the toner base particle has a toner core and a shell layer covering a surface of the toner core, the toner core contains the binder resin, The toner according to claim 1 , wherein the shell layer contains the charge control agent.
3. the shell layer contains hydrophobic resin particles and positively charged resin particles, The toner according to claim 2 , wherein the positively chargeable resin particles contain the charge control agent.
4. The toner according to claim 3, wherein the number average primary particle diameter of the hydrophobic resin particles is 20 nm or more and 50 nm or less.
5. 4. The toner according to claim 3, wherein the number average primary particle diameter of the positively charged resin particles is 25 nm or more and 60 nm or less.
6. The toner according to claim 3 , wherein the content of the hydrophobic resin particles is from 0.5 parts by mass to 5.0 parts by mass with respect to 100 parts by mass of the toner core.
7. The toner according to claim 3 , wherein the content of the positively chargeable resin particles is from 0.05 parts by mass to 3.0 parts by mass with respect to 100 parts by mass of the toner core.
8. The toner according to claim 1 , wherein the binder resin further comprises a polyester resin.
9. The toner according to claim 8 , wherein the binder resin has a content of the polyester resin of 20.0% by mass or more and 40.0% by mass or less.
10. 1. A method for producing a toner comprising: a toner core preparation step of preparing a toner core containing a binder resin; a shell layer forming step of forming a shell layer on the surface of the toner core to obtain a toner base particle; and an external addition step of adhering an external additive to a surface of the toner base particles to obtain the toner particles, The glass transition point of the binder resin is 20° C. or higher and 65° C. or lower, The binder resin contains a specific styrene-(meth)acrylic resin, the content of the specific styrene-(meth)acrylic resin in the toner base particles is 50.0% by mass or more and 95.0% by mass or less, The specific styrene-(meth)acrylic resin has an acid value of 2.5 mgKOH / g or more and 30.0 mgKOH / g or less, the shell layer contains hydrophobic resin particles and positively charged resin particles, the shell layer forming step comprises dispersing the toner cores, the hydrophobic resin particles, and the positively charged resin particles at a treatment temperature of 55° C. or higher and 78° C. or lower.
Citation Information
Patent Citations
Method of producing toner, and toner
JP2007025655A